Frost resistance of peach promising varieties (Prunus persica L.) as bred by Nikitsky Botanical Garden - А. В. Смиков; Н. В. Мєсяц (Plant Varieties Studying and Protection)
This article is dedicated to frost resistance studies of 27 hybrid forms of peach of Nikita Botanical Garden breeding and 3 control zoned varieties. The studies enabled to single out 3 hybrid forms of early maturity: Zlatogor х Uspar-1 80-367, Laureat х Zlatogor 73-3 and Zsi-yan-shuj mi-tao х Collins 13 st. III 1/3; 3 hybrid forms of medium maturity time:Veteran self-pollinated, Veteran х Redheaven 81-136 and Laureat хZlatogor 73-6; 1 hybrid form of late maturity: (Tovarisch х I 1 26-76 Nektadiana) 85-197, that displayed high frost resistance of flower buds. The marked out forms are worth considering as a source of increased frost resistance of flower buds to be used in breeding programs